Story-a-Garment: Skins Storied for a Body in Pain - Ibrahim-Jerrywo, Salma (Auckland University of Technology, 2025)
My Insides, turned skin. My carcass, your protector. Your shield. Your armour. Traces of me linger within the folds of your hide, seeping through the punctured wounds of your flesh. My story, engraved into the seams, unravelling at the hems. I’ve become…more than. Story-a-Garment: Skins Storied for a Body in Pain takes the position of being hunted and alienated through highlighted life experiences. Seeking a way out, I use personal antagonistic experiences to story a garment in my exploration into a hybrid fashion and spatial design practice. Alternating between the eye of the prey and predator, both sides of the story take place through a spectrum of methods: story, escape, obsess, and morph. Narratives shift, unravel, and mutate within the series of works. Here, the story comes to life through worldbuilding. Multiple lifeforms threaded across evolving structures, garments, and adorned bodies. This work is to be situated in an escape environment. To be gawked at, stared upon. Questioned.